2007
DOI: 10.1007/s00586-007-0515-7
|View full text |Cite
|
Sign up to set email alerts
|

Disc height reduction in adjacent segments and clinical outcome 10 years after lumbar 360° fusion

Abstract: Adjacent segment degeneration (ASD) is discussed to impair long-term outcome after lumbar interbody fusion. Nevertheless the amount and origin of degeneration and its clinical relevance remain unclear. Only little data is published studying quantitative disc height reduction (DHR) as indicator for ASD in long-term follow-up. Forty patients (23 men, 17 women) (group 1: degenerative disc disease, n = 27; group 2: lytic spondylolisthesis, n = 13) underwent lumbar 360°instru-mentation and fusion between 1991 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
56
3
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(67 citation statements)
references
References 34 publications
6
56
3
1
Order By: Relevance
“…There is an increasing concern, regarding the long-term consequences of these asymptomatic changes; however, correlation of ASD and clinical outcome is still unclear [46,52].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There is an increasing concern, regarding the long-term consequences of these asymptomatic changes; however, correlation of ASD and clinical outcome is still unclear [46,52].…”
Section: Discussionmentioning
confidence: 99%
“…ASD incidence is higher in patients with transpedicular instrumentation (12.2-18.5%) compared with patients fused with other forms of instrumentation or with no instrumentation (5.2-5.6%). Evidence of radiographic degeneration, however, does not necessarily lead to a poor clinical outcome of surgery [21,52]. A recent clinical study [52] showed that the incidence of ASD (DH reduction) in the first cephalad adjacent segment 10 years following 360°i nstrumented lumbar fusion averaged 21%, while in the second adjacent level averaged 16%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations